Blood cholinesterase activity levels of farmers in winter and hot season of Mae Taeng District, Chiang Mai Province, Thailand - Surat Hongsibsong (2018)
© 2015 Springer-Verlag Berlin Heidelberg Organophosphate and carbamate pesticides have been widely used by farmers for crop protection and pest control. Inhibition of acetylcholinesterase (AChE) in erythrocyte and butyrylcholinesterase (BChE) in plasma is the predominant toxic effect of organophosphate and carbamate pesticides. Mae Taeng District, Chiang Mai Province, is one of the large areas of growing vegetables and fruits. Due to their regular exposure to these pesticides, the farmers are affected by this toxicity. The objective of the study was to examine the AChE and the BChE activity levels in the blood of 102 farmers for comparison of exposure in two cropping seasons, winter and hot. Blood samples were collected in December 2013 (winter) and April–June 2014 (hot). A total of 102 farmers joined the study, represented by 76 males (74.5 %) and 26 females (25.5 %). The age of most of the farmers was 53.4 ± 8.7 years. Out of 102, 21 farmers used carbamate pesticides. The results showed that the AChE and the BChE activity levels of all the farmers were 3.27 ± 0.84 Unit/mL and 2.15 ± 0.58 Unit/mL, respectively. The AChE and the BChE activity levels in males were 3.31 ± 0.88 Unit/mL and 1.97 ± 0.60 U/mL, respectively, during winter and 3.27 ± 0.82 Unit/mL and 2.15 ± 0.58 U/mL, respectively, during the hot season, and AChE and the BChE activity levels in females were 3.27 ± 0.82 U/mL and 2.44 ± 0.56 U/mL, respectively, during the hot season. The cholinesterase activity levels, both AChE and BChE, in the male farmers’ blood had significant difference between the two seasons, while in the case of the female farmers, there was significant difference in the BChE activity levels, at p < 0.05. The BChE activity level was found to significantly correlate with self-spray (p < 0.05), which implies that the BChE activity decreased when they sprayed by themselves. The cholinesterase activity levels of the present study were lower than those of the other studies, which may be an indication of some chronic effect of exposure to anticholinesterase pesticides. Thus, it is recommended that the use of pesticides be decreased, together with increase in the awareness of the impact of pesticides on health; also recommended is regular monitoring of blood cholinesterase.